2017
DOI: 10.1038/s41598-017-08444-6
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle and adipose tissue morphology, insulin sensitivity and beta-cell function in diabetic and nondiabetic obese patients: effects of bariatric surgery

Abstract: Obesity is characterized by insulin-resistance (IR), enhanced lipolysis, and ectopic, inflamed fat. We related the histology of subcutaneous (SAT), visceral fat (VAT), and skeletal muscle to the metabolic abnormalities, and tested their mutual changes after bariatric surgery in type 2 diabetic (T2D) and weight-matched non-diabetic (ND) patients. We measured IR (insulin clamp), lipolysis (2H5-glycerol infusion), ß-cell glucose-sensitivity (ß-GS, mathematical modeling), and VAT, SAT, and rectus abdominis histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 47 publications
6
86
2
1
Order By: Relevance
“…Additionally, successful demonstration of targeting to white and brown adipose tissues opens the door to encapsulating different therapeutics in these particles for targeting fatty tissue in diseases where adipose tissue is defective. One possible disease state is diabetes, where adipose tissues shows chronic inflammation 275 . A classical marker of the chronic inflammation in diabetic fatty tissue is crown like structures produced by macrophages 276 .…”
Section: Chapter 53: Discussionmentioning
confidence: 99%
“…Additionally, successful demonstration of targeting to white and brown adipose tissues opens the door to encapsulating different therapeutics in these particles for targeting fatty tissue in diseases where adipose tissue is defective. One possible disease state is diabetes, where adipose tissues shows chronic inflammation 275 . A classical marker of the chronic inflammation in diabetic fatty tissue is crown like structures produced by macrophages 276 .…”
Section: Chapter 53: Discussionmentioning
confidence: 99%
“…Insulin sensitivity and declining beta-cell function are the key pathophysiologic drivers in T2DM. Previous reports have demonstrated improvements in both parameters in subjects undergoing BS [29], but as yet the effects of a gastro-duodenal bypass liner on these key determinants of glucose metabolism are not well investigated. The results of the first of such studies suggest that positive effects on glucose metabolism occur rapidly after DJBL implantation [27] and that these effects are comparable to those after BS.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle biopsy demonstrated increased fat infiltration and adipocyte hypertrophy and a reduction in the number and size of mitochondria. Individuals with type-2 diabetes (relative to obese individual without type-2 diabetes) demonstrated impaired ß-GS, intracapillary neutrophils, and higher intramyocellular fat, adipocyte hypertrophy, and crownlike structures in in both VAT and SAT (95). After bariatric surgery, insulin-resistance and lipolysis both decreased.…”
Section: Adipose Tissuementioning
confidence: 99%
“…The tissue density of crown-like structures is positively related to adipocyte size, independent of the degree of obesity (93,94). In a sentinel study, Camastra et al (95) investigated the impact of bariatric surgery on (1) measured insulin-resistance (insulin clamp), (2) lipolysis (2H5-glycerol infusion), (3) ßcell glucose-sensitivity (ß-GS, mathematical modeling), and (4) cellular substructure (electron microscopy). Investigators found that pre-surgical subcutaneous fat (SAT) and visceral fat (VAT) demonstrated fibrosis/necrosis, small mitochondria, free interstitial lipids, and a thickened capillary basement membrane (95).…”
Section: Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation